2009
DOI: 10.1111/j.1600-0838.2007.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Using sport to promote HIV/AIDS education for at‐risk youths: an intervention using peer coaches in football

Abstract: The purpose of this study was to investigate the effectiveness of an ongoing AIDS education intervention program (EMIMA) using peers in a sport context. A secondary purpose was to determine whether a mastery-based motivational strategy would enhance the effectiveness of the peer coaches. A quasi field experimental study was employed in which at-risk children in Dar es Salaam in Tanzania (N 5 764) were recruited (average age 5 13.6 years) and were randomly grouped into two treatment groups and two control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 30 publications
0
99
0
2
Order By: Relevance
“…To our knowledge, our study is the first to report differences in frequency of condom use associated with an HIV prevention programme through sports as the two previously published evaluations of soccer-based programmes merely reported on changes in knowledge, attitudes and intentions (Clark, Friedrich, Ndlovu, Neilands, & McFarland, 2006) or used a composite scale to describe changes in condom experience (Maro, Roberts, & Sorensen, 2009). The analysis presented in this paper begs two key questions: Does the association of MYSA membership with increased condom use point to a causal effect?…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, our study is the first to report differences in frequency of condom use associated with an HIV prevention programme through sports as the two previously published evaluations of soccer-based programmes merely reported on changes in knowledge, attitudes and intentions (Clark, Friedrich, Ndlovu, Neilands, & McFarland, 2006) or used a composite scale to describe changes in condom experience (Maro, Roberts, & Sorensen, 2009). The analysis presented in this paper begs two key questions: Does the association of MYSA membership with increased condom use point to a causal effect?…”
Section: Discussionmentioning
confidence: 91%
“…PeacockVillada et al 2007, Maro et al 2009, Nicholls 2009). While generic youth-oriented NGOs in Kamwala and Chawama involved peer leaders in the delivery of a variety of activities, it was within sporting organizations and programmes that young people most frequently held positions of responsibility.…”
Section: Local Sport-for-development Approaches and Issuesmentioning
confidence: 92%
“…Based on these results the authors concluded that under the right conditions, sport had the potential to contribute to both personal and social development, but more research was needed to investigate the long term effects (SDP IWG, 2007). Maro et al (2009) investigated the effect of an AIDS education program using peers in a football context. A randomized quasi-experimental design was used.…”
Section: Part I: Football As a Tool For Developmentmentioning
confidence: 99%
“…United Nations define development as a process of enlarging people's choices and increasing the opportunities available to all members of society, particularly in countries considered to be low income (UN, 2003). Research shows that using sport as a tool for development has the potential to contribute to both personal and social development (Maro et al, 2009;SDP IWG, 2007). In Kenya most of the youth football leagues are organized by non-governmental organizations (NGO) that use football as a tool for development.…”
Section: Introductionmentioning
confidence: 99%